Korban Perbudakan Modern Sebagai Mustahiq Zakat: : Kontekstualisasi Penafsiran Term al-Riqab - Fathan, Ahmad Ali Syauqi; Musyarrofah; Nafi' Mubarak (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2025)
This study seeks to re-examine the meaning of al-riqa>b as one of the eligible recipients (mustah}iq) of zakat and sadaqah in the context of modern slavery. Historically, al-riqāb refers to slaves who were emancipated through zakat and sadaqah, as outlined in Qs. al-Tawbah (9: 60) and Qs. al-Baqarah (2: 177). However, following the formal abolition of slavery, there is an urgent need to reinterpret this category to ensure its relevance to contemporary forms of social and economic oppression. Using a contextual approach, this study evaluates the eligibility of victims of forced labor, forced marriage, debt bondage, and human trafficking as modern representations of al-riqāb. The findings indicate that individuals who suffer exploitation, loss of freedom, and structural entrapment may be categorized as modern al-riqāb and thus qualify for zakat and sadaqah. Meanwhile, other forms of hardship that do not fit this category may still be supported through other zakat or sadaqah.